Koninklijk Vlaams Conservatorium: traditie en vernieuwing - Persoons, Guido (Antwerpen Hogeschool Antwerpen, 1998)
The 'Koninklijk Vlaams Conservatorium' (Royal Flemish Conservatoire) 1898-1998 aims to go beyond cataloguing isolated historical facts, but to interpret them in the wider perspective of the real impact of the main higher music institution in Flanders, first as the Royal Flemish Conservatoire and, since 1998, as a college department.It was a hard struggle for up to Dutch-language Arts Education to reach the highest level. Its elevation to Royal Flemish Conservatory in 1898 remains a mark of cultural awareness in Flanders. Not only that pre-history is evoked, but later images of KVC's interaction illustrate cultural life in various fields and international exchanges.The overview ends with the integration of KVC into the Department of Dramatic Arts, Music and Dance of the Hogeschool Antwerpen since 1 September 1995. (Translated with Deepl.com)
1898 School - Conservatorium - Hogeschool 1998
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Music history; Music education; Antwerp (Belgium)